INTERCULTURAL COMMUNICATION IN INTERETHNIC FAMILIES IN PAGUTAN BARAT VILLAGE, MATARAM CITY - Widiantari, Made; Jelantik, Sayu Kadek; Astraguna, I Wayan (Journal of Digital Media Communication, 2024)
This research is based on phenomena observed by the researchers where families with different ethnic backgrounds maintain harmony within the family and community despite their diverse ethnicities. Therefore, this research analyzed the factors, forms, and impacts of intercultural communication in interethnic families in Pagutan Barat Village, Mataram City. The method used is qualitative, employing non-participant observation for data collection. Primary data sources include three married couples, community leaders, neighborhood heads, and religious figures, gathered through semi-structured interviews and documentation. Secondary data sources include books, journals, and photographs. The analysis involves three stages: data reduction, data presentation, and conclusion drawing. The study utilizes Communication Accommodation Theory and Interpersonal Communication Theory to analyze the research questions. The results indicate that love and family are the main factors leading to interethnic marriages. The forms of communication used include verbal and non-verbal communication, intrapersonal communication, and interpersonal communication. The positive impacts of intercultural communication in interethnic families are the integration of values and traditions, uniting differences through joint activities, conflict resolution, and space management, the use of a common language, and a broader community. However, the negative impacts include potential internal conflicts arising from differences in religious symbols, rituals, and space arrangements.